EFFICIENCY IMPROVEMENT OF TRANSPORT SERVICE BY TROLLEY BUSES BASED ON THE LEVELS OF THEIR POWER DEMAND - Aulin, V. V.; Plokhov, I. O.; Holub, D. V. (Science and Transport Progress, 2014)
Purpose. Use efficiency improvement of trolley buses in passenger traffic based on power levels of electric energy input and terms adjustment of their maintenance. Methodology. In order to achieve this goal conformance of electric energy input by trolleybus to the transported amount of passengers taking into account characteristics of the route is offered to establish. The major indicators of the trolleybus operation are: speed of a race on lines, number of tractive motor firing, voltage and amperage in the network that were taken with accountants from a dashboard. Research results were tabulated and recorded with DVR. Along with the study of power consumption of electric energy input by a trolleybus passenger count was carried out too. Findings. The directly proportional dependence between the level of energy consumption by a trolleybus and the number of passengers for constant performance route was determined. Originality. As the criteria for evaluating the effectiveness of the trolleybus operation on the route is proposed to use the ratio between electricity consumption and number of passengers for these characteristics of the route. This is confirmed experimentally. The obtained formulas give the possibility to balance the force work and consequently the volume of energy consumption during the trolleybus movement on the rise and the descent. Practical value. The proposed criterion can be used to adjust the terms of maintenance on the individual program, that means individual maintenance (IM). Type of work performed at the IM should be determined on the basis of diagnostic data of the vehicle (V). The principles of IM were formulated: 1) the primary task is planned and preventative strategy to identify and eliminate troubleshooting and technical actions; 2) operational control of the vehicle (V) technical condition on the basis of prediction of its state using the proposed criteria, that takes into account the dependence of power consumption to the number of passengers in the characteristics of the route; 3) individual approach to evaluate the technical condition of each specific vehicle (V); 4) individual prediction of the frequency of the maintenance and vehicle condition.